A gerontologist's idea of the world, time, and the curse for the president T.S. Eliot, Robert Frost, Wilfredo Pascua Sanchez, Wallace Stevens, Jose Garcia Villa, and their poems from or about old age - Cosocot, Ian Rosales (2011)
Old age does not always engender a positive poetic response. In specific works by five poets - T.S. Eliot's "Gerontion," Robert Frosts "Directive", Wallace Stevens' "The Man With the Blue Guitar," Wilfredo Pascua Sanchez's "Adarna," and Jose Garcia Villa's "The Anchored Angel" - we get disparate views of the aging condition. We get sense that old age is the ripe time for reflection on the meaning of the march of time. The poets in this study render their very specific judgment of the meaning of time, ranging from the wistful to the raging to the quietly accepting. This paper observes that the younger poets (at the time of the writing of the works in question) are relentless in their view old age as a time of decay and decreptitude; the older poets (at the time of the writing of the work in question) are gentler, more optimistic about growing old; the passage of time for these poets has a moral dimension, with the past almost always perfect, and the present and the future awash in chaos and corruption; and that for these poets, there are ways of mitigating or making sense of this chaoes in life, and the older personas in the poems consider these two as the best methods: spirituality and art.
Keywords: Poetry (Literary form)